Identification of Myostatin Gene Polymorphism (MSTN|Taq1) Exon-2 in Pitalah Duck Using The PCR-RFLP Method - Subekti, Kusnadidi; Salsabila, Winanti; Samara, Nada Iswari; Arlina, Firda (Buletin Peternakan, 2025)
This study aimed to identify the polymorphism of the exon-2 myostatin gene (MSTN) in Pitalah ducks using the PCR-RFLP (Polymerase Chain Reaction-Restriction Fragment Length Polymorphism) method. 28 blood samples of Pitalah ducks were used in this study. Blood samples were extracted using Intron Biotechnology's Intron G-SpinTM Total DNA Extraction Kit protocol. The DNA extraction results were then amplified using a pair of primers, namely the Forward: 5' TCCACTTGTTACTGATGCTGT-3' primer and the Reverse: 5'- TAGGGAAATGGAGGCACAGG-3' primer, with a fragment target of 700 bp. Furthermore, the amplified product is restricted using the Taq1 enzyme, which recognizes the cutting site on T|CGA. Based on the results of the study, two genotypes were found, namely 89.29% truncated homozygous (+/+) and heterozygous (+/-), as well as 10.71% of the total sample used, while untruncated homozygous genotypes (-/-) were not found in this study. Meanwhile, the allele frequency (+) was 0.946, the allele frequency (-) was 0.054, and the observed heterozygosity value was greater than the expected heterozygosity value (Ho>He). This study concludes that the myostatin exon-2 gene in Pitalah ducks is polymorphic and is in Hardy-Weinberg equilibrium.